Efektivitas Peran Pemerintah Daerah dalam Mencegah Terjadinya Pemutusan Hubungan Kerja pada Masa Pandemi Covid-19 di PT. Bali Maya Permai Kabupaten Jembrana - Dewa Ketut Swanjaya Tirta; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2022)
The existence of the Covid-19 Pandemic, in addition to taking many lives, also has a broad impact on the economy. Many companies experience bankruptcy and layoffs. Only companies that are quick to implement efficiency policies can survive and not give massive losses to the workforce. PT. Bali Maya Permai in this pandemic situation, resulted in employment problems. This study aims to examine the effectiveness of the implementation of industrial relations during the Covid-19 pandemic at PT. Bali Maya Permai and reveals the role of the Jembrana Regency Government in preventing layoffs during the Covid-19 pandemic at PT. Bali Maya Permai. This study is designed using empirical legal research with a sociological juridical approach. The data used are primary and secondary legal data obtained through interview techniques, observation and questionnaires, and archives. Furthermore, the data are analyzed qualitatively. The result of the study shows that industrial relations during the Covid-19 pandemic at PT. Bali Maya Permai is not completely running well because there are still labor problems. The preventive juridical and socio-economic steps taken by the Jembrana district government to prevent termination of employment were not entirely successful, because layoffs were still occurring. In this regard, it is recommended that employers respect the rights of workers so that industrial relations can run well and harmoniously.